1984
DOI: 10.3733/hilg.v52n02p057
|View full text |Cite
|
Sign up to set email alerts
|

Response of soils to sodic and saline conditions

Abstract: SALINE AND SODIC SOIL CONDITIONS reduce the value and productivity of soils in the arid and semiarid regions of the world. Accumulation of soluble salt in the soil solution im poses stress on growing crops that can lead to decreased yields and, in severe cases, com plete crop failure. Accumulation of dispersive cations such as sodium and, possibly, potassium in the soil solution and the exchange phase affects soil physical properties such as structural stability, hydraulic conductivity, and infiltration rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
287
0
15

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(312 citation statements)
references
References 88 publications
10
287
0
15
Order By: Relevance
“…With regard to chemical effects, cation valence is known to affect the permeability of soils containing clays (e.g., [17][18] and to influence the morphology of clay aggregates (e.g. , [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to chemical effects, cation valence is known to affect the permeability of soils containing clays (e.g., [17][18] and to influence the morphology of clay aggregates (e.g. , [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Lebron et al (2002) found that hydraulic conductivity decreased sharply as ESP approached 5%. An ESP of only 2.2% can cause a 70% decrease in infiltration rate (Shainberg & Letey 1984). Soils with a high clay or silt content might be expected to be more sensitive to increased ESP than sandy soils.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
“…However, soil pH is already greater than 6.0 in the HC treatment without lime having been applied at any time over the 32 years to all but one of the HC plots; thus the addition of lime to supply Ca 2þ and increase soil pH further is not an agronomic option. The addition of gypsum is a possible management strategy to minimize the impact of slurry (Shainberg & Letey 1984;Halliwell et al 2001;Lebron et al 2002). Gypsum can provide the Ca 2þ needed to exchange for Na þ and K þ and maintain a higher electrolyte concentration in solution; it has been shown to improve soil physical conditions (Shainberg & Letey 1984;Sumner 1993;Yu et al 2003) and P retention (Vidal et al 2003).…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaching of salts by irrigation water is inhibited by an unstable soil structure and decline in soil permeability (Shainberg and Letey, 1984). The toxicity of Na ion leads to proper consideration of sodium-divalent cations exchange selectivity and its influence.…”
Section: Objectivesmentioning
confidence: 99%